Transforming agriculture for human and planetary health in Asia - Fan, Shenggen (2018)
Shenggen Fan SPECIAL EVENT Transforming Agriculture: Experiences and Insights from Brazil and Beyond Co-Organized by IFPRI and Embrapa MAY 15, 2018 - 12:15 PM TO 01:45 PM EDT